The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/2211-5463.13193
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of gut microbial dysbiosis in adults with myeloid leukemia

Abstract: Dysregulation of gut microbiota is implicated in the pathogenesis of various diseases, including metabolic diseases, inflammatory diseases, and cancer. To date, the link between gut microbiota and myeloid leukemia (ML) remains largely unelucidated. Herein, a total of 29 patients with acute myeloid leukemia (AML), 17 patients with chronic myeloid leukemia (CML), and 33 healthy subjects were enrolled, and gut microbiota were profiled via Illumina sequencing of the 16S rRNA. We evaluated the correlation between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…Therefore, we further performed FMT in AML mice and found that AML-FMT aggravated the progression of AML compared with that in Con-FMT mice. A recent study by Yu et al 33 reported that the bacterial diversity was increased and no depletion of Faecalibacterium was found in AML, which is different from our results. These differences may be due to the regional and gender diversities which have been reported by other studies 34 37 .…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we further performed FMT in AML mice and found that AML-FMT aggravated the progression of AML compared with that in Con-FMT mice. A recent study by Yu et al 33 reported that the bacterial diversity was increased and no depletion of Faecalibacterium was found in AML, which is different from our results. These differences may be due to the regional and gender diversities which have been reported by other studies 34 37 .…”
Section: Discussioncontrasting
confidence: 99%
“…Ji et al [ 31 ] found significant enrichment of Clostridium_sensu_stricto_1 in a model of necrotic enterocolitis in neonatal mice. It was also found to be significantly enriched in IBS syndrome [ 32 ] and leukemia [ 33 ]. This is the first report of Clostridium_sensu_stricto_1 in cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yu and co-authors [75] observed a higher relative abundance of Actinobacteria, Acidobacteria, and Chloroflexi in the gut microbiota of myeloid leukemia compared to healthy controls; this observation confirms an alteration of the microbiota in tumor conditions. This enrichment is in line with our experimental findings, not only about Chloroflexi, but also regarding the presence of Actinobacteria in CRC biopsies (Fig.…”
Section: Discussionmentioning
confidence: 58%